Characteristics of Charcoal Briquwttes from Palm Oil Midrib and Coconut Midrib with Tapioka Glue - Bayu Nugroho; Faizah Hamzah; Raswen Efendi; Angga Pramana (Universitas PGRI Semarang, 2021)
The purpose of this study aims to get the best combination of palm oil midrib and coconut midrib in making charcoal briquettes. The study was conducted experimentally using a complete randomized design method consisting of 5 treatments and 3 replications. The treatments in this study were the ratio of palm oil midrib and coconut midrib charcoal as follows: KSK1 (100:0), KSK2 (75:25), KSK3 (50:50), KSK4 (25:75) and KSK5 (0:100). The parameters observed were density, water content, ash content, vapour content, bound carbon content and heating value. The result of palm oil midrib and coconut midrib shells had a significant effect on density, water content, ash content, vapour content, bound carbon content and heating value. Based on the results of the analysis, the best treatment in this study were KSK4 of palm oil midrib and coconut midrib (25:75) with a density of 0,58 g/cm3, water content 5,82%, ash content 5,87%, evaporating content 15,01%, bound carbon content 79,12%, and heating value content 6596,65 cal/g.